2020
DOI: 10.1016/j.jss.2019.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Goals of Care Discussions for the Imminently Dying Trauma Patient

Abstract: Background: A structured family meeting (FM) is recommended within 72 h of admission for trauma patients with high risk of mortality or disability. Multidisciplinary FMs (MDFMs) may further facilitate decision-making. We hypothesized that FM within three hospital days (HDs) or MDFM would be associated with increased use of comfort measures. Materials and methods:We reviewed all adult trauma deaths at an academic level 1 trauma center from December 2014 to December 2017. Death in the first 24 h or on nonsurgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…16 Early goals of care discussions and multidisciplinary family meetings are associated with increased comfort care measures for imminently dying trauma patients. 17 Additionally, there is an increasing proportion of geriatric trauma patients; and age can be a major factor in deciding whether to implement palliative care during admission to the ICU. 10 In our study, the surgical intensivist-led team took care of more geriatric patients over 65 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…16 Early goals of care discussions and multidisciplinary family meetings are associated with increased comfort care measures for imminently dying trauma patients. 17 Additionally, there is an increasing proportion of geriatric trauma patients; and age can be a major factor in deciding whether to implement palliative care during admission to the ICU. 10 In our study, the surgical intensivist-led team took care of more geriatric patients over 65 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Request for palliative care consultation at our institution is provider-dependent and often occurs in close proximity to death. 7 We theorize that palliative care consultation is called to help transition to comfort measures when it is determined that further care is futile and the intensivist ceases to document CCT. We did not access hospital billing data for this study and could not determine if 99 291 or 99 292 was actually billed, or whether these codes were attributed to other teams, such as palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…A single-center retrospective cohort study analyzing critical care documentation in trauma patients at the end of life was performed at our mature, urban, academic, level 1 trauma center. 7 Criteria were selected to identify dying patients who would be eligible for critical care billing prior to death. We screened all adult patients who were included in our prospectively maintained trauma registry and identified all patients who died between December 2014 and December 2017.…”
Section: Methodsmentioning
confidence: 99%
“…The needs assessment was performed as a retrospective review over a 3-year period to identify potential areas for improvement. 16 We studied the use of multidisciplinary team meetings, palliative care consult use, and code status changes in trauma patients who died of all ages. This study demonstrated that early multidisciplinary care had tangible benefits: fewer patients died as 'full code', and there was more use of comfort measures; we also noted these services were used earlier in younger patients but were delayed in older patients.…”
Section: Methodsmentioning
confidence: 99%